Analysis of Maturity Alignment of Business Strategy with Information Technology at SAMSAT Bengkulu City Using Strategic Alignment Maturity Model (SAMM) - Kurnia Anggriani; Ferzha Putra Utama; Stern Imanuel Kristian; Arie Vatresia; Putra Bismantolo (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2025)
Motor vehicle tax payments represent a substantial portion of regional income. However, recurrent delays in motorbike tax payments, notably in the Kandang Limun sub-district of Bengkulu City, pose a significant threat to regional development. This research aims to address these delays by predicting and implementing effective strategies. Using the RapidMiner application and the Artificial Neural Network (ANN) method, a delay rate of 36.14% was predicted. The study incorporates interviews to propose several strategies, including enhancing websites, improving offline and online services, implementing Drivethru services, and using SMS Blast notifications to combat delays. To evaluate the feasibility of these strategies, the research employs the Strategy Alignment Maturity Model (SAMM). The assessment at BPKD reveals a maturity level of 4, signifying an ability to improve and manage processes effectively.The maturity assessment suggests that the proposed strategies for overcoming delays are well-aligned with BPKD's capabilities. They have demonstrated a robust alignment between IT and business strategies, leveraging IT to enhance performance, and conducting thorough business and IT evaluations.In addition to the maturity assessment, the research offers suggestions and evaluation strategies. These encompass the adoption of biometrics for authentication, implementation of chatbots, Samsat self-service kiosks, real-time vehicle monitoring, and the introduction of automatic tax programs.